What you aren't seeing : how using your hidden potential can help you discover the leader within : the inspiring story of Herb Greenberg - Sweeney, Patrick, 1952- (McGraw-Hill Education, 2015)
Helps you to discover your potential and leverage it to drive organizational success. This book provides a three-step action approach to seeing and tapping into your leadership potential - and that of your entire organization by 1) Seeing Inside Yourself 2) Seeing New Possibilities and 3) Seeing Far and Wide.